2018
DOI: 10.1016/j.chiabu.2018.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Are negative/unrealistic parent descriptors of infant attributes associated with physical abuse?

Abstract: Parents' perceptions of child behavior influence their responses to the child and may be important predictors of physical abuse. We examined whether infants 12 months of age or younger who were described with negative or developmentally unrealistic words were more likely than other infants to have been physically abused. As part of a prospective observational multicenter study investigating bruising and familial psychosocial characteristics, parents were asked to (1) describe their child's personality, and (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Associations between negative descriptors of the child and poor outcomes were also found by Young and colleagues (2018) who demonstrated that negative descriptions of a child postnatally are associated with risk for child maltreatment. Our work builds upon these findings by demonstrating that negative descriptions of the child's future personality can indicate risk for poor parent–child interaction before the child is born.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Associations between negative descriptors of the child and poor outcomes were also found by Young and colleagues (2018) who demonstrated that negative descriptions of a child postnatally are associated with risk for child maltreatment. Our work builds upon these findings by demonstrating that negative descriptions of the child's future personality can indicate risk for poor parent–child interaction before the child is born.…”
Section: Discussionsupporting
confidence: 64%
“…Findings from a study investigating risks for infant abuse revealed that infants between 7 and 12 months of age were at greater risk for physical abuse by parents who described their personalities using negative or developmentally inappropriate words (e.g., “needy” and “drama queen”) (Young et al., 2018). In another study, the tendency to label novel, ambiguous infant facial expressions with negative emotion words was associated with reduced sensitive parenting behavior with their own child (Dayton et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, descriptions of their caregiving experiences can indicate more subtle underlying hostility. Such negative experiences of the child or the parenting role are associated with physical abuse and poor outcomes for the child (Young et al., 2018) and this is most likely mediated by harsh parenting behavior (Nix et al., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although cross-sectional and retrospective studies provide correlation or association with child abuse and neglect, they do not provide evidence on the cause and effect of abuse or other variables that may mediate the cause and effect. Risk factors associated with abuse include a caretaker’s history of child abuse, negative caretaker perceptions of their child, caretaker affect or behavioral problems including substance abuse, caretaker cognitive and affective deficits, housing instability, non-biological caregiver in the home, chaotic or volatile family situations (Douglas & Mohn, 2014; Duffy, Hughes, Asnes, & Leventhal, 2015; Lindberg, Beaty, Juarez-Colunga, Wood, & Runyan, 2015; Miyamoto et al, 2017; Wathen & MacMillan, 2013; Young et al, 2018). Protective factors that increase family strengths and reduce the likelihood of child abuse and neglect include supportive social networks, stable family relationships, nurturing parenting skills, parental employment and adequate housing (Kumpfer & Magalhães, 2018; Saul et al, 2014; Schofield, Lee, & Merrick, 2013; Stith et al, 2009; Swenson & Chaffin, 2006).…”
Section: Introductionmentioning
confidence: 99%